Change The Sandler Way - Knox, Hamish (Ascent Audio, 2020)
There are four stages of transition that all of us experience when making a successful adjustment to a new work situation . . . and eight common, potentially negative consequences that are likely to accompany any organizational change initiative. Leaders who understand these four stages, and who understand the human dynamics behind the eight most common challenges, can improve their odds of success. In this powerful, accessible resource for leaders, management consultant Hamish Knox gives managers an overview of the four stages of transition that all of us experience when making a successful adjustment to a new work situation. They are: 1. Denial; 2. Resistance; 3. Exploration; and 4. Commitment. Knox also argues that there are eight common, potentially negative consequences that are likely to accompany any and every organizational change initiative. They are: 1. A sense of loss; 2.Confusion and ambivalence; 3. Reduced trust; 4. Increased concern about survival; 5. Communication problems; 6. Lower productivity; 7. Turnover; and 8. Strong emotional responses. Based on the work of David Sandler, creator of the Sandler Selling System.